A proposed program of the high school [Ifugao Academy] for the improvement of Ifugao economy - Uyan, Venancio T. 1918- ([Quezon City s.n.], 1958)
This is a study of the economic conditions, problems and needs of a rural community and the program of a general high school. It aims at formulating a proposed program of the high school for the improvement of the economy of the community.
56-B; and l. 102
Bibliography: l. 211.
Leaves numbered in duplicate: l. 16-A & 16-B; 56-A
Thesis (M.Ed.)--University of the Philippines, 1958
Typescript (carbob copy)
Vita
Keywords: Ifugao Academy; Ifugao -- Economic conditions; Community and school